Parents’ Perception on Printed Modular Distance Learning in Canarem Elementary School: Basis for Proposed Action Plan - Olivo, Marilyn G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This was a descriptive study which determined and analyzed the perceptions of parents on the printed modular distance learning in an elementary school. There were 50 parent respondents selected via convenience sampling. Parents’ perceptions were along the manner of distributing modules, retrieval of modules, time allotment for learning activities, the learning activities in the module, assessment and observance of safety and health protocols in the distribution and retrieval of modules. Questionnaires were distributed to the parents through the Purok Leaders who were responsible in the distribution and retrieval of the learning modules. Weighted mean was used to analyze the responses of the parents in the questionnaires. Finding revealed that parents mostly agreed to the strategies in the distributing modules, retrieval of modules, time allotment for learning activities, the learning activities in the module, assessment and highly agreed to the observance of safety and health protocols in the distribution and retrieval of modules. However, parents claimed that time allotment in the completion of learning activities was insufficient since the activities were so many. In addition, some parents claimed that they could not understand some topics in the module so they could not help their children in answering the learning activities. The research then recommended for a review of the learning activities and conduct seminar for parents to guide them in assisting their children during their “classes “at home. An action plan was developed to improve the implementation of the modular learning in the new normal.